Soros Meets Students (Camera 1) - Part 3
Final part of the recording of George Soros in a public conversation with students on November 9, 2004 in the CEU Auditorium. The discussion is moderated by Rositsa Bateson (Vice President for Student Services). Topics covered: US elections, the war in Iraq, the current and future role of the Open Society Institute (OSI), regional issues of Central and Eastern Europe, the former Soviet Union and Central Asia, and Central European University itself.